Type of Personality, Food Consumption and Physical Activity Levels as Determinants of Overweight and Obesity among Urban Adolescents - Alfian Yusuf; Suryanto Suryanto; Annis Catur Adi; M. G. Bagus Ani Putra (Health Notions, 2018)
Obesity is a global epidemic, it was health issues that must be addressed immediately. There was a very significant increase in the prevalence of overweight and obesity of adolescents. Several studies showed that social support related to eating disorders and physical activity of adolescents causes of overweight and obesity. Other study showed that personality contributes to health outcomes and it was associated with a controllable risk factor such as obesity. The aim of the study was to measure the relationship of personality type, fatty food consumption, and physical activity level to overweight and obesity among adolescents. We used a case-control design with 270 subjects. Case population was vocational or senior high school students with overweight or obesity and the control population was vocational or high school students without overweight or obesity. Data analysis used chi-square test with 95% confidence level (α = 0.05) and Odds Ratio (OR). The results showed that there was no significant relationship between personality type and overweight or obesity (p> 0.05). There was a significant relationship between the consumption of fatty foods (p = 0.001), the level of physical activity (p = 0.040) and overweight or obesity among adolescents. Keywords: Adolescents, Overweight, Obesity, Personality, Fatty foods, Physical activity